Analisis Tindak Tutur Ekspresif pada Program Kompetisi Pendidikan Clash of Champions by Ruangguru - Muhammad Irsyad Hamid Nugroho; Tri Maria Hastuti; Dhenok Aurorra Candra Pradwipta; Widyadhana Benda S. Nismara; Yulian Akbar Rizki Nur Fazri; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Bagas Kurnianto (Student Scientific Creativity Journal, 2025)
The Clash of Champions educational competition program by Ruangguru not only offered academic challenges but also provided a high level of verbal interaction, particularly in the use of expressive speech. This study aims to analyze the use of expressive speech in the program, focusing on episodes one to five. Expressive speech refers to utterances that convey the speaker's emotions, such as praise, gratitude, or apologies. The method used in this study is qualitative descriptive, utilizing a data-collection technique based on assent with a derivative of participant observation. Data analysis is conducted using the pragmatic method to identify the types of expressive speech present. The study also used pragmatic approaches to describe the speech of others as well as that of expressive speech. The study indicates that there are eight types of expressive speech, including acts of flattery, praise, gratitude, belittlement, guilt, complaint, and apology. Flattering speech is found to be the most dominant, providing emotional support for the competition participants. It is hoped that this study will contribute to a better understanding of language use in educational and competitive contexts, fostering a positive and supportive atmosphere in the learning process.